Modeling and optimization of water mist system for effective air-cooled heat exchangers. (March 2022) - Park, Hyundo; Roh, Jiwon; Oh, Kwang cheol; Cho, Hyungtae; Kim, Junghwan
Highlights: The CFD model was developed and validated with results of the experimental device. We solved the low cooling performance of ACHEs and corrosion problem simultaneously. Optimum amounts of water for cooling to the target temperature were presented. The CFD model was applied to design the commercial process. Abstract: Air-cooled heat exchangers (ACHEs) are one of the most efficient and widely used equipment for heat exchange. However, the main disadvantages of ACHEs are their heat exchange performance is decreased by high ambient air temperature (Ta ), especially on summer season. To solve this problem, a water mist system that sprays an amount of water is applied to ACHEs. However, the water mist system causes corrosion problems of the peripheral devices. Therefore, it is crucial to find a proper water mist system with optimized operating conditions that improve the cooling effect without corrosion. Herein, we developed the CFD model to find the optimal amount of water sprayed. Cooling effect and water evaporation ratio according to the amount of water sprayed and Ta were calculated using the CFD model. As a result of the calculation, the amount of water that gives the target cooling effect as all water evaporates is 3.364 kg/h and 7.928 kg/h at Ta of 303.15 K and 313.15 K, respectively. This study provides the optimal amount of water sprayed on the water mist system considering the cooling effect and corrosion according to Ta, and it can apply to the commercial processes. Graphical abstract: Image, graphical abstract